Wastewater Pollution from Cruise Ships in the Adriatic Sea - Tina Perić; Pavao Komadina; Nikola Račić (Promet (Zagreb), 2016)
The global growth of cruise tourism has brought increasing concern for the pollution of the marine environment. Marine pollution from sanitary wastewater is a problem especially pronounced on large cruise ships where the number of people on board may exceed 8,000. To evaluate future marine pollution in any selected period of time it is necessary to know the movement of ships in the Adriatic Sea. This paper presents the problem of marine pollution by sanitary wastewater from cruise ships, wastewater treatment technology and a model of cruise ship traffic in the Adriatic Sea considering MARPOL Annex IV areas of limited wastewater discharge. Using the model, it is possible to know in advance the routes of the cruisers and retention time in certain geographic areas. The data obtained by this model can be used as input parameters for evaluation model of wastewater pollution or for evaluation of other types of pollution from cruise ships.